Sustainable Local Bioeconomies: A Nature-based strategy to bridge Well-being gaps. A Methodological Approach to identify, structure, and develop local Bioeconomies - Sanchez-Mejia, Myriam (Cuadernos de Administración, 2025)
Colombia is recognized as a country world pantry of food for humanity (BID, 2014) for its natural wealth, while the indices of monetary poverty and hunger, exceed 40% (DANE, 2021). The country is no stranger to world crises: social, environmental, and economic, especially in terms of poverty, hunger, loss of biodiversity and climate crises. In Colombia, biodiversity and ecosystem services are not "valued" as part of socio-ecological dynamics (Rincón-Ruiz A. et al (edits) 2021), at the microeconomic level, and are not remunerated, at the service of well-being, in construction of sustainable local bioeconomies. Additionally, value is not always added to local biodiversity due to ignorance or non-recognition (Sánchez M., 2016), which could explain the contrast of monetary poverty in territories of special richness in biodiversity and ecosystem services. The social, environmental/climate and economic crises raise the imperative need of change in the state intervention and its effectiveness (Mazzucato, 2022) to contribute to the well-being of communities. In this context, the development of local Bioeconomies is proposed as a strategy to close well-being gaps, with base on nature-based solutions. Valuing biodiversity and ecosystem services at the local level (IPBES, 2022) is a necessary step to address the issue.